Fog computing and Edge computing: An edge over cloud computing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
IoT and its applications are assumed to be as rich source of data. On daily basis, devices come across the internet to exchange information and thus gather, store information from nearby environment to process accordingly. Cloud computing can store massive amount of information that can be anywhere and anytime in the world. Data can be accessed adequately due to its high computation and storage power. Cloud computing model is centralized in nature. Therefore, cloud architecture is not able to respond to low latency and high mobility requirements. There are various challenges high response time, high bandwidth that had emerged in cloud architecture. And to resolve these challenges, new technologies like fog computing and edge computing has been emerged. In this paper, cloud technology has been compared with fog computing and edge computing model. This paper is divided into two parts. The first part contains characteristics of fog computing, cloud computing and edge computing.The second part contains the difference among all the computing paradigms.